Psychometric analyses of the Tower of London planning task reveal high reliability and feasibility in typically developing children and child patients with ASD and ADHD. Issue 2 (17th February 2020) - Unterrainer, Josef M.; Rahm, Benjamin; Loosli, Sandra V.; Rauh, Reinhold; Schumacher, Lena V.; Biscaldi, Monica; Kaller, Christoph P.
ABSTRACT: The Tower of London (TOL) is probably the most often used assessment tool for planning ability in healthy and clinical samples. Various versions, including our proposed standard problem set, have proven to be feasible and reliable in adults. In contrast, reliability information for typically developing (TD) children and neurodevelopmental disorders during childhood are largely missing. Also, it would be highly desirable to attain a problem set that can be used across the whole lifespan. Therefore, here we examine reliability of our proposed standard problem set using a computerized TOL version in 178 TD children (two different samples), 49 children with high-functioning autism spectrum disorder (ASD) and 56 children with attention-deficit/hyperactivity disorder (ADHD) (age ranges of each group 6 to 13 years), and 130 young adults (age range 18 to 32 years). Greatest lower bound estimates of reliability were adequate to high in the two samples of TD children (.76 and .80) and high to very high in patients (ASD: .90; ADHD: .83). In young adults, all reliability indices were adequate to high. Moreover, a subset of four- and five-move problems exhibited sufficient performance variability and high part-whole correlations with the complete problem set in all samples. These findings demonstrate the reliability of the presented TOL problem set in both clinical and non-clinical child samples. A clinically feasible subset of four- and five-move problems is reflective of overall planning performance at all ages, hence enabling comparisons of planning ability within and between developmental samples across almost the whole lifespan.